1973
DOI: 10.1128/jb.116.1.141-145.1973
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Deoxyribonucleic Acid Replication in a Temperature-Sensitive Mutant of B. subtilis : Evidence for a Transcriptional Step

Abstract: A mutant of Bacillus subtilis unable to initiate a new round of replication at 45 C has been described. Here we show that inhibition of DNA synthesis in this mutant is reversible and that DNA synthesis is resumed at low temperature, even in the presence of chloramphenicol. Initiation of a new replication cycle thus can occur in the absence of protein synthesis. A thermolabile component required for initiation therefore appears to be synthesized at 45 C in an inactive form and can be activated at 30 C in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
1

Year Published

1974
1974
1995
1995

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 28 publications
(32 reference statements)
1
23
1
Order By: Relevance
“…As discussed below, this could indicate thai ether factors may also inhibit DNA replication after the induction of the Stringent Response. Importantly, in the controi experiment, both strains appear to fully replicate their chromosome in the presence of chloramphenicoi but replicalicn is completely blocked in the presence of rifampicin, as found previousiy in the dna637 mu(anf after transfer from 45 C to 30 C (Laurent, 1973;Seror et ai, 1986). These results reflect the fact that in dnaB37strain synchronized for DNA replication, the requiremenl for protein synthesis for initiation has been satisfied by growth at permissive temperature, whilst RNA synthesis is still required to initiate a new round of replication.…”
Section: Residuai Dna Synthesis In Wild Type and Irtp Strains During supporting
confidence: 64%
“…As discussed below, this could indicate thai ether factors may also inhibit DNA replication after the induction of the Stringent Response. Importantly, in the controi experiment, both strains appear to fully replicate their chromosome in the presence of chloramphenicoi but replicalicn is completely blocked in the presence of rifampicin, as found previousiy in the dna637 mu(anf after transfer from 45 C to 30 C (Laurent, 1973;Seror et ai, 1986). These results reflect the fact that in dnaB37strain synchronized for DNA replication, the requiremenl for protein synthesis for initiation has been satisfied by growth at permissive temperature, whilst RNA synthesis is still required to initiate a new round of replication.…”
Section: Residuai Dna Synthesis In Wild Type and Irtp Strains During supporting
confidence: 64%
“…The initiation of a new round of deoxyribonucleic acid (DNA) replication at the origin of the bacterial chromosome requires the synthesis of ribonucleic acid (RNA). Evidence for this includes the following: (i) both rifampin and streptolydigin inhibit initiation after the time when chloramphenicol is no longer inhibitory in Escherichia coli (20,26); (ii) Laurent (22) has found that reinitiation in a Bacillus subtilis thermoreversible DNA initiation mutant is sensitive to rifampin and streptolydigin but not to chloramphenicol; (iii) Messer and co-workers (27,45) have isolated a putative origin-RNA from E. coli, the synthesis ofwhich is independent of the dnaC gene product but is influenced by the product of the dnaA gene; and (iv) reinitiation in a thermoreversible dnaA mutant is sensitive to rifampin but not to chloramphenicol, and the sensitivity to rifampin is due specifically to RNA polymerase inhibition by rifampin (47).…”
mentioning
confidence: 99%
“…When only deoxyribonucleic acid (DNA) synthesis has been arrested, chromosome initiation may be induced as soon as permissive conditions are restored (20). DNA initiation requires two steps, chloramphenicol (CAP) sensitive and CAP resistant (11,23), in addition to a transcriptional event (10,13,18). Genetic data confirm the complexity of this process since two different groups of initiation mutations have been identified in Escherichia coli (7,24,26) and Bacillus subtilis (9,25).…”
mentioning
confidence: 98%
“…If the culture is returned to 30 C, the inhibition of replication is reversed, and DNA synthesis is resumed synchronously. Reinitiation can occur in the presence of CAP, suggesting that the temperaturesensitive protein required for initiation is synthesized at 45 C in an inactive form and can be renatured to 30 C in the absence of protein synthesis (13). However, even after a prolonged period at 45 C, no more than one replication cycle can be initiated when the bacteria are returned to 30 C in the presence of CAP.…”
mentioning
confidence: 99%